Koncepcja zrównoważonej karty wyników dla Wrocławia - Nieplowicz, Maria (The Conception of the Balanced Scorecard for Wrocław, 2008)
The main goal of the article is to introduce the possibilities of using the Balanced Scorecard as a tool that describes the strategy of the city's development and helps to monitor its realization. The article presents the conception of the Balanced Scorecard for Wrocław. In order to adjust the traditional concept of the Balanced Scorecard to Wrocław needs, its perspectives have been corrected as to quantity as well as their meaning. There are five perspectives suggested: perspective of politics, perspective of citizen, perspective of internal processes, perspective of commerce, and perspective of development. The article shows strategic aims, strategy map, and the structure of Balanced Scorecard for Wroclaw. The process of creating, implementing and cascading the Balanced Scorecard was described in details.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 100-112